How Internet usage contributes to livelihood resilience of migrant peasant workers? Evidence from China. (December 2022) - Chen, Hong; Chen, Chien-ping; Li, Yuheng; Qin, Lijian; Qin, MingShuai
Abstract: Access to employment through the Internet matters a great deal to stabilise the livelihood of migrant peasant workers in Chinese cities. This study examines how Internet usage affects the off-farm income of migrant peasant workers by constructing a random effects model for the period 2010–2016. Research findings corroborate that Internet usage has significantly increased the off-farm income of migrant peasant workers and the positive impact of Internet usage on income is stronger for migrant peasant workers than for their urban flexible-employed counterparts. The positive impacts of Internet usage on migrant peasant workers' income vary regarding region, gender, and educational level. It is concluded that Internet usage has helped improve the livelihood resilience of migrant peasant workers in China. Highlights: Internet usage significantly increased the off-farm income of migrant peasant workers. The impact is stronger for the migrant workers compared with their urban counterparts. The positive impacts of internet usage on migrant workers' income vary in regions. The positive impact is stronger on female income compared with male counterparts. The positive income impacts of internet usage increase in education level.